Parental Roles in Early Childhood Special Education for Children with Disabilities: A Case Study of Dera Ghazi Khan (Journal of Asian Development Studies, 2024)
This study explores the role of parents in supporting their disabled children's engagement in early childhood special education programs. Parents are expected to participate in several sessions and collaborate closely with special education teachers to develop individualized plans tailored to their child's needs. This research helps examine the factors that influenced and restricted parental engagement by various obstacles, including societal challenges, parent-teacher dynamics, children, and families. This study investigates the role of parental involvement in the education of children with disabilities, focusing on three primary objectives: (1) to examine the extent and nature of parental responsibilities in supporting their children's educational needs, (2) to explore how parental involvement influences engagement and participation in educational activities, and (3) to identify the factors that impact parental engagement and support for special education. Using a quantitative research design, the research examines the relationship between socioeconomic factors, parental involvement, and children's access to and participation in special education services. A correlational research design was employed to analyze quantitative data collected from 120 parents through structured questionnaires. The study's findings emphasize that are actively involved in their children's educational experiences; they can assist their children in flourishing by supplying them with the resources necessary to achieve academic and social success.